A Rare Cause of Ascites-Disseminated TB with Peritonitis in a Middle-Aged Female - Sahathevan Vithoosan; Ponnudurai Shanjeeban; Joseph Philip Anpalahan; Paramarajan Piranavan; Harindra Karunatilake; Ananda Jayanaga (Case Reports in Gastrointestinal Medicine)
Background. Disseminated tuberculosis (TB) has been increasingly recognized in adults in the recent times due to increased prevalence of immune suppression. Here we describe a case of 47-year-old female who presented with disproportionate ascites where the diagnosis of disseminated TB was delayed. Case Report. A 47-year-old previously healthy female presented with generalised body swelling with disproportionate ascites and loss of appetite and weight for four-month duration. She denied any contact or past history of TB and reported no respiratory symptoms. Physical examination revealed significant ascites. There was no lymphadenopathy or hepatosplenomegaly. Respiratory system examination was normal. Her Erythrocyte Sedimentation Rate (ESR) was above 100. Tuberculin skin test was positive with 17mm. Contrast Enhanced Computed Tomography (CECT) abdomen revealed chronic liver disease with ascites. Diagnostic laparoscopy was in favour of miliary TB and the peritoneal biopsy revealed granulomatous inflammation with caseous necrosis, suggestive of TB. The patient was started on antituberculosis treatment and subsequently improved. Conclusion. TB peritonitis due to disseminated TB should be considered in the differential diagnosis of disproportionate ascites. Even though the diagnosis is difficult, diagnostic laparoscopy and biopsy is very helpful. It is important to have an early diagnosis since delay in treatment can be detrimental in most cases.